Applied element modelling of unreinforced and reinforced concrete masonry walls under blast loading. (May 2023) - Gouda, Ahmed; ElSayed, Mostafa; Salem, Hamed; Attia, Walid; Elansary, Ahmed
Abstract: Masonry walls are the first defense line against exterior explosions in buildings; however, no adequate guidelines are currently available for the analysis and design of these walls under such extreme loading. In this paper, a comprehensive applied element model (AEM) is developed and validated to investigate the behaviour of both reinforced (RMWs) and unreinforced (URMWs) concrete masonry walls under blast loading. A single degree of freedom (SDOF) model is also developed to estimate their pressure-impulse diagram for concrete masonry walls. The developed models are utilized to conduct a parametric study by analyzing 30 walls with different design parameters (boundary conditions, dimensions, compressive strength, as well as reinforcement ratio) under various blast loadings. Crack pattern, fundamental period, support rotation, as well as pressure–displacement and pressure-impulse diagrams for the analyzed walls were compared. The boundary conditions and compressive strength had the most and least significant influence on the behaviour of walls. The two-sides-supported walls experienced severe cracks compared to the four-sides-supported walls. Fundamental period decreased by 74% when the wall thickness increased from 100 mm to 250 mm for either URMWs or RMWs. Resistance of a wall with dimensions of 3 × 7 m was less than that of a 5 × 2 m wall by 81% and 77% for URMW and RMW, respectively. The SDOF model showed that URMWs and RMWs with dimensions of 5 × 2 m had the maximum pressure-impulse response limit compared to the other walls. The average increase in the support rotation was 200% and 380% when the charge weight increased from 5 kg to 15 kg for URMWs and from 15 kg to 150 kg for RMWs, respectively. Using reinforcement ratio greater than 0.85% considerably improved the performance of RMWs.